Navigating ethical challenges in Indonesian digital public relations practices - Wachid, Ivan Bimantoro; Wulandari, Maulina Pia; Nasution, Zulkarnain (Universitas Bunda Mulia, 2024)
The emergence of Digital Public Relations (PR) management has revolutionized the way in which corporations communicate with their public, utilizing digital platforms to provide more dynamic and interactive communication. Nevertheless, this digital revolution has also resulted in a multitude of ethical dilemmas and challenges. This study aims to analyze the ethical dimensions of Digital Public Relations management in Indonesia, with a particular focus on the challenges encountered and the approaches employed for navigating them. This qualitative study employs in-depth interview as data collection method with two experienced Indonesian PR practitioners to gain comprehensive and detailed observations. The findings highlight various notable challenges in digital PR management, encompassing the need to uphold transparency in communications and guarantee social responsibility in every PR strategy. This study suggests an Ethical Digital Public Relations model that includes three fundamental ethical values: transparency, privacy management, and social responsibility, based on the aforementioned findings. Ultimately, the study recommends PR practitioners to adhere to these three values in order to successfully address ethical dilemmas and strengthen the credibility as well as reliability of their digital PR management. By upholding these values, PR practitioners can effectively handle ethical challenges and make a beneficial impact on the growing field of digital public relations.